Hypocalcemic cardiomyopathy: A case report - Wen, Yi; Luo, Xiaolin (Frontiers in Cardiovascular Medicine, 2022)
Hypocalcemia and its related symptoms are common manifestations in postsurgical hypoparathyroidism, but patients with hypocalcemia manifested as heart failure is rare and few cases are reported in the literature. Here we reported a 58-year-old female with hypoparathyroidism and uncontrolled hypocalcemia after thyroidectomy, presented with acute heart failure, accompanied with enlargement and reduced ejection fraction of left ventricle. She was refractory to guideline-directed medical therapy for heart failure including digitalis and diuretics. However, her symptoms resolved and cardiac function improved dramatically after normalization of serum calcium level. This rare case highlights the pivotal role of calcium in maintaining cardiac function and the importance of treating underlying reversible causes of heart failure. For patients with hypoparathyroidism, it is essential to get standard treatment to avoid development of heart failure and hypocalcemia related syndromes.